A route to magnetically separable nanocatalysts: Combined experimental and theoretical investigation of alkyl substituent role in ligand backbone towards epoxidation ability. (10th November 2016) - Chattopadhyay, Tanmay; Chakraborty, Aratrika; Dasgupta, Sanchari; Dutta, Arnab; Menéndez, M. Isabel; Zangrando, Ennio
Abstract : We have prepared two chiral Schiff base ligands, H2 L 1 and H2 L 2, and one achiral Schiff base ligand, H2 L 3, by treating 2, 6‐diformyl‐4‐methylphenol separately with ( R )‐1, 2‐diaminopropane, ( R )‐1, 2‐diaminocyclohexane and 1, 1′‐dimethylethylenediamine, in ethanolic medium, respectively. The complexes MnL 1 ClO4 (1 ), MnL 2 ClO4 (2 ), MnL 3 ClO4 (3 ), FeL 1 ClO4 (4 ), FeL 2 ClO4 (5 ) and FeL 3 ClO4 (6 ) have been obtained by reacting the ligands H2 L 1, H2 L 2 and H2 L 3 with manganese(III) perchlorate or iron(III) perchlorate in methanol. Circular dichroism studies suggest that ligands H2 L 1 and H2 L 2 and their corresponding complexes have asymmetric character. Complexes1 –6 have been used as homogeneous catalysts for epoxidation of alkenes. Manganese systems have been found to be much better than iron counterparts for alkene epoxidation, with3 as the best catalyst among manganese systems and6 as the best among iron systems. The order of their experimental catalytic efficiency has also been rationalized by theoretical calculations. We have observed higher enantiomeric excess product with catalysts1 and4, so they were attached to surface‐modified magnetic nanoparticles to obtain two new magnetically separable nanocatalysts, Fe3 O4 @dopa@MnL 1 and Fe3 O4 @dopa@FeL 4 . They have been characterized and their alkene epoxidation ability has been investigated. These catalysts can be easily recovered by magnetic separation and recycled several times without significant loss of catalytic activity. Hence our study focuses on the synthesis of a magnetically recoverable asymmetric nanocatalyst that finds applications in epoxidation of alkenes and at the same time can be recycled and reused. Abstract : Schiff base complexes were synthesized and characterized and then attached to Fe3 O4 nanoparticles to make magnetically separable nanocatalysts which were characterized and used as efficient asymmetric catalysts for epoxidation of alkenes. They exhibited outstanding recyclability for several consecutive reaction runs.